Endogenous Opioids in Crohn’s Disease - Adrian Martyniak; Andrzej Wędrychowicz; Przemysław J. Tomasik (Biomedicines, 2023)
Caring for patients with Crohn’s disease (CD) is a serious challenge in modern medicine. The increasing incidence of CD among adolescents and the severe course of the disease create the need for new methods of diagnosis and therapy. Endogenous opioids are a group of low molecular weight chemical compounds with analgesic and anti-inflammatory properties. Endorphins, enkephalins, and dynorphins may have potentially beneficial effects on the course of CD. Previous research data on this topic are inconsistent. Some authors have reported an increase in the concentration of leukocytes during the course of inflammatory bowel disease (IBD) while others have described a downward trend, explained by DPP-IV enzyme activity. Even fewer data are available on plasma endo-opioid level. There is also a lack of comprehensive studies that have assessed the endo-opioid system in patients with IBD. Therefore, the objective of this study was to measure the serum concentrations of human β-endorphin, human proenkephalin (A), and human big dynorphin in CD patients in the acute phase of the disease, during hospital treatment, and in the remission state. All determinations were performed using ELISA kits. The results of our study showed that the concentrations of all the tested endo-opioids, especially β-endorphin and proenkephalin (A), were reduced in adolescents with CD compared to those in the healthy control group, during the acute phase of the disease, and in the remission state. Modulation of the endogenous opioid system and the use of selective nonnarcotic agonists of opioid receptors seems to be promising goals in the future treatment of CD.